2013
DOI: 10.1002/eji.201343711
|View full text |Cite
|
Sign up to set email alerts
|

Human plasma cells express granzyme B

Abstract: While studying the plasma cell (PC) compartment in human tonsils, we identified that immunoglobulin kappa or lambda chain-expressing PCs are the main cells expressing granzyme B (GrzB). In vitro studies revealed that activated B cells differentiated into GrzBexpressing PCs when co-cultured with macrophages and follicular helper T cells. This effect could be reproduced on combined stimulation of IL-15 (produced by macrophages) and IL-21 (produced by T follicular helper cells) in a STAT3-dependent manner. Wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 49 publications
1
22
0
Order By: Relevance
“…61 Interestingly, CD138 has also been shown to be associated with GzmB production, regulatory activity, and IL-21 dependence. 57 In conclusion, we have demonstrated that TOLs have a higher absolute number of GzmB + B cells with a plasma cell2like phenotype and with dose-dependent suppressive properties through the GzmB pathway. B cells decrease T cell proliferation and induce their apoptosis, two processes that may contribute to a tolerogeneic environment.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…61 Interestingly, CD138 has also been shown to be associated with GzmB production, regulatory activity, and IL-21 dependence. 57 In conclusion, we have demonstrated that TOLs have a higher absolute number of GzmB + B cells with a plasma cell2like phenotype and with dose-dependent suppressive properties through the GzmB pathway. B cells decrease T cell proliferation and induce their apoptosis, two processes that may contribute to a tolerogeneic environment.…”
Section: Discussionmentioning
confidence: 56%
“…These data are reinforced by the effective STAT3 phosphorylation in B cells from tolerant recipients, 14 a key signal for the generation of GzmB activated B cells. 57 Finally, the fact that tolerant recipients have a lower level of IL-21 + CD4 + T cells, and that B cells from these patients alone (and not HVs and STAs) increase IL-21 production by CD4 + T cells, strongly suggests a negative feedback loop in these patients, increasing excessive B cell activation and inflammation and allowing regulation to take place. Bregs are able to control the immune response, but an excessive reaction from these cells may also promote tumor cell growth or chronic infection.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Moderate positivity for granzyme B was observed in the cytoplasm of immune cells in the stroma (mainly plasma cells and mast cells, 19,20 ) of less than half of the samples (33% unpretreated, 43% pretreated) (Fig. 2E).…”
Section: Foxp3mentioning
confidence: 99%
“…Interestingly, it has been reported in humans that granzyme B + B cells accumulated specifically in tissues and have been suggested to play a critical role in early antiviral immune responses, in the regulation of autoimmune mechanisms, and in cancer immunosurveillance (45)(46)(47). Additionally, it has recently been shown that BCR and IL-21 signaling without an efficient CD40-CD40L ligation leads to the generation of granzyme B + B cells that induce immune dysfunction in solid tumor eradication (45,(48)(49)(50) or in HIV patients (51).…”
Section: Igmmentioning
confidence: 99%